Morphological analysis of myocardial bridging leading to myocardial ischemia: myocardial coronary coupling - Yu, Guanghao; Ming, Zhaokai; Qiao, Dan; Cheng, Zhiguo; Li, Liandi; Guo, Wei; Ye, Xiaoqiang; Ma, Wei; Chen, Guangxin; Ren, Mingming; Xing, Jian; Tan, Wenchang; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMyocardial bridge (MB) is a segment of an otherwise extramyocardial blood vessel that traverses the myocardium. This congenital condition typically lacks obvious clinical manifestations during adolescence. However, as individuals age, the accumulated myocardial pressure on the coronary arteries can lead to non-obstructive coronary ischemia, angina pectoris, and even heart failure. Early diagnosis is crucial for assessing the risk of cardiovascular events.Methods This study performed a morphological analysis of MB in 75 patients using dual-source Computed Tomographic Angiography (CTA). Through geometric three-dimensional reconstruction, measurements and statistical analyses were conducted on muscle bridge length, depth, length-to-depth ratio, cross-sectional area, and coronary artery curvature. ResultsThis study explores the morphological differences among normal individuals, those with superficial MB, and those with deep MB during diastole and systole under varying conditions of myocardial coronary coupling. The study found that the compression degree is greatest in the deep MB group, with the average compression level being approximately 17 times that of normal individuals and about 4.6 times that of patients with superficial MB.DiscussionThe differences in the average cross-sectional area are more significant than those in the minimum cross-sectional area. The depth of the MB is more closely related to the degree of compression, suggesting that clinical intervention and attention should be focused on deep MBs.